(untitled) (Journal of Mathematical Study, 2025)
Degenerate complex Monge-Ampère equations arise naturally in the study of geometry of singular varieties. In this paper, we prove gradient estimate and W^3,p estimate for a class of degenerate complex Monge-Ampère equations.